HUBUNGAN ANTARA PERILAKU SAFETY RIDING DAN STRES KERJA TERHADAP KECELAKAAN KERJA PADA PENGENDARA OJEK ONLINE KOMUNITAS X TEMBALANG - Sulaeman Apka Joddy; Ida Wahyuni; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2022)
Traffic accidents are still a serious problem in Indonesia, where cases tend to increase every year. Motorcycles are the type of vehicle that dominates traffic accidents that occur. One group of motorcycle riders who have a high risk of having an accident is an online motorcycle taxi driver. For online motorcycle taxi drivers, traffic accidents are work accidents. This study aims to analyze the relationship between safety riding behavior and work stress on accidents among online motorcycle taxi drivers in the X Tembalang Community. A cross sectional approach and data analysis using the chi-square method. The data was taken using a questionnaire instrument with the number of samples determined through the total sampling method of 30 people. The results showed that as many as 53.3% of respondents had safe driving behavior and as many as 70% of respondents had moderate work stress levels and the rest had low work stress levels. There was a relationship between safety riding behavior and work accidents (p-value = 0.017), there was no relationship between work stress and work accidents (p-value = 0.389) on online motorcycle taxi drivers in the X Tembalang community. The company should supervise the implementation of rider partner safety riding and involve the driver partner in setting policies. Riders should also implement and remind each other about safety riding and keep in touch to create a good psychological work environment to reduce work stress levels.